Effectiveness of a mixed lifestyle program in couples undergoing assisted reproductive technology: a study protocol - Padideh Malekpour; Robab hasanzadeh; Mojgan Javedani Masroor; Reza Chaman; Zahra Motaghi (BMC, 2023)
Abstract Background The desire for fertility is the manifestation of yearning for immortality. Infertility and assisted reproductive technology (ART) expose couples to great affective, anxiety, stress, and financial burden. Increasing evidence emphasize the impact of lifestyle on infertility. One of the most crucial factors affecting the fertility process is the nutrition patterns, the amount and quality of physical activities, emotional problems management; modulate stressors, relief from anxiety, and the living conditions of couples. Most ART treatment interventions in Iran are not integrated into lifestyle programs. Therefore, this research will investigate the impact of mixed fertility health-promoting programs in couples who use ARTs. Methodology/Design This study entails three steps. The first step includes the systematic review of literature on a health-promoting lifestyle in infertile couples undergoing ARTs, a systematic review of observational studies and interventions in couple's lifestyle, then, a systematic review of qualitative studies on infertility in couples and their lifestyle, and in the final step couple's life style literature systematically will evaluate in Iran. In case of failure to obtain the required results from systematic reviews, cross-sectional studies will be carried out to determine the lifestyle of infertile couples receiving ARTs. In the second stage, by holding a panel of experts, an intervention is planned based on the results of the previous stages in order to improve the lifestyle of couples. In the final step, the designed intervention will be administered as a random clinical trial-on ART candidates, in intervention or control groups in one of Iran University of Medical Sciences hospitals. Afterward, the data's will be evaluated by using standard questionnaires, that include health-promoting lifestyle questionnaire (HPLII), Beck's depression inventory (BDI), international physical activity questionnaire-short form (IPAQ-SF), and food frequency questionnaire (FFQ). The statistical analysis will be carried out in SPSS software. During the study, subjects meeting the inclusion criteria were randomly selected and randomized into the intervention and control groups. The health-promoting lifestyle training program will be executed for the intervention group while the standard care program is administered to the control group. The content of this program will be obtained from the consensus opinions of the expert panel. The program includes diet recommendations, physical activity, and stress management. Appropriate time, frequency, duration and number of activities will be considered. Communication with subjects will be possible through private meeting special comfort room. Support to the participants will also be through clinical visits social media, SMS and phone calls. Nutritional changes, physical activity amount, anxiety and stress level, abdominal circumference (AC), and body mass index (BMI) will be measured after the completion of the specified time interval. The initial outcome includes examining chemical pregnancy (2 weeks after the transmission) and clinical pregnancy by ultrasound (6 weeks after). The secondary outcome will be live birth rate. Retrieved oocyte and embryo numbers will also be reported. Discussion Health-promoting lifestyle programs are essential in assisted reproductive technologies to improve pregnancy results and live birth. These programs in association with in-vitro fertilization (IVF) influence the outcome of fertilization. In addition, enhancing parental health leads to healthy pregnancy outcome. Despite the frequency of lifestyle risk factors, employing proper methods helps reduce anxiety and stress, modify dietary patterns, and perform qualitatively and quantitatively balanced physical activities. In addition, having coping skills and mental health management methods, in nowadays modern world challenges seems crucial and effective in solving fertility problems and reducing them before pregnancy.